Antimicrobial Resistance Profile and Associated Factors of Group B Streptococci Colonization among Pregnant Women Attending Antenatal Clinics in Jigjiga, Southeast Ethiopia - Tesfaye, Addisu; Melese, Addisu; Derbie, Awoke (International Journal of Microbiology, 2022)
Background. Streptococcus agalactiae (group B Streptococcus, GBS) is one of the causes of maternal and neonatal morbidity and mortality in many parts of the world. It is associated with severe maternal and neonatal outcomes. The colonization rate, associated factors, and antimicrobial sensitivity (AST) profile of GBS among pregnant women in Eastern Ethiopia is less studied. Methods. A cross-sectional study was conducted from 1st March to 30th May, 2021 in Jigjiga. A total of 182 pregnant women with a gestational period of ≥36 weeks were included. A structured questionnaire was used to collect data on the participants’ demographic and clinical history. Vaginal-rectal samples were collected by brushing the lower vagina and rectum with a sterile cotton swab for bacteriological culture. An antimicrobial sensitivity test (AST) was performed using the Kary-Bauer disk diffusion method. Data were entered and analyzed using SPSS version 25. The logistic regression model was used to find out factors associated with GBS colonization. Results. GBS colonization among pregnant women attending antenatal care was at 15.9% (29/182). The AST result showed that the majority of the isolates were sensitive to vancomycin (96.6%), chloramphenicol (96.6%), ampicillin (93.1%) azithromycin (89.7%), and penicillin (86.2%). In contrast, the isolates were found to be resistant to ceftriaxone, erythromycin, ciprofloxacin, clindamycin, and tetracycline at 17.2%, 20.7%, 27.6%, 27.6%, and 34.5%, respectively. Multidrug resistance (MDR) was noted in 4 isolates (13.79%). GBS colonization was significantly associated a with history of preterm labor (<37 weeks of gestation) (AOR = 3.87, 95% CI = 1.36–10.9) and a history of prolonged ruptured membrane (>18 hr.) (AOR = 3.44, 95% CI = 1.34–8.83). Conclusions. The colonization rate of GBS was considerably high among pregnant women attending antenatal care in the present study area. The observed antimicrobial resistance for the common drugs and the reported MDR level calls for routine screening of pregnant women for GBS and actions to minimize antimicrobial resistance (AMR) should be strengthened.